Pancreatic lipase enzymatic activity in broilers fed with Roystonea regia fruit meal included in the ration. Technical note - Vives, Yesenia; Martínez, Madeleidy; Alberto, Maryen; Hernández, Yasmila (Cuban Journal of Agricultural Science, 2020)
An amount of 40 male broilers was used for determining the activity of pancreatic lipase enzyme from broilers that consume Roystonea regia fruit (royal palm nut meal) meal in the ration. A completely randomized design was applied with four treatments, which consisted of replacing 0, 5, 10 and 15 % for royal palm nut meal. At 42 d, they were sacrificed to obtain the pancreas and enzymatic activity of pancreatic lipase was determined. Diet effect was observed in this indicator, which was higher in broilers consuming royal palm nut meal, compared to control diet (1983 vs. 2500, 2566, and 3283 mL of NaOH/min/mg of protein, respectively) (P <0.05). It is concluded that royal palm nut meal inclusion in diets for broilers increases the activity of pancreatic lipase enzyme to digest lipids in the gastrointestinal tract. Key words: enzymatic activity, lipids, broilers fowl, royal palm nut meal